(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Urinary tract infection is a common and serious clinical problem in newborns. Renal scarring, hypertension, and even kidney failure can be prevented by early diagnosis and treatment of urinary tract infection. Jaundice is an important and sometimes the presenting feature of urinary tract infection. Objectives:To evaluate the frequency and bacterial profile of urinary tract infection in full term and preterm newborns with hyperbilirubinemia in the first two week of life, and the relation with some demographic parameters. Methods:Seventy two jaundiced neonates were studied. Hematocrit, white blood cell count, reticulocyte count, blood group and Rh, bilirubin (direct and total), Coombs test, and glucose 6-phosphate dehydrogenase level were evaluated. Septic screen and thyroid function test, urinalysis and culture for all patients. Results:Twenty two (30%) out of 72 complain from urinary tract infection. Majority of them were full term 15 (68%), and Body weight > 2.5 Kg 12 (54%), fifteen delivered by normal vaginal delivery (68%). Breast feeding was recorded in 12 (54%), total serum bilirubin level above 20 mg/dl was found in 19 (86%). Gestational age, Normal Vaginal Delivery, Type of feeding, and total serum bilirubin level more than 20 mg/dl had significant correlation with urinary tract infection in jaundiced neonates, while birth weight was not significant. Commonest isolated bacteria was Escherichia coli in 11 (50%), staphylococcus infection in 2 cases (9.1%) have significant correlation with male gender. Ultrasound result was only positive in one (4.5%) neonate and showed pelvi-calceal obstruction. Conclusion:Urinary tract infection is common among jaundiced neonates particularly in males. Escherichia coli is the commonest causative bacteria. Gestational age, normal vaginal delivery, type of feeding, and total serum bilirubin level more than 20 mg/dl had significant correlation with urinary tract infection in jaundiced neonates, while birth weight was not significant. Key word:Neonatal jaundice, hyperbilirubinemia, UTI